2012
DOI: 10.1177/0004867411432851
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and neurocognitive profiles of subjects at high risk for psychosis with and without obsessive–compulsive symptoms

Abstract: The OCS manifested in UHR individuals was associated with a more severe clinical symptomatic presentation, including lower global functioning and more psychotic symptoms. On the other hand, those with UHR-OCS performed more poorly on some cognitive tests. The features that distinguish the groups can be used for developing prognoses and intervention strategies for the heterogeneous UHR group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 55 publications
4
21
0
1
Order By: Relevance
“…The severity of OC symptoms and degree of functional impairment were not correlated in either sample (Niendam et al, 2009a;Hur et al, 2012). However, seemingly conflicting results were found when patients in these studies were dichotomised into high and low OC symptom groups.…”
Section: Anxietymentioning
confidence: 90%
See 1 more Smart Citation
“…The severity of OC symptoms and degree of functional impairment were not correlated in either sample (Niendam et al, 2009a;Hur et al, 2012). However, seemingly conflicting results were found when patients in these studies were dichotomised into high and low OC symptom groups.…”
Section: Anxietymentioning
confidence: 90%
“…Niendam et al (2009b) reported no significant differences between the two groups in global, social or role functioning or on any measures of clinical symptom severity. In contrast, Hur et al (2012) reported that patients in the high OC symptom group exhibited poorer global functioning. However, patients in the high OC group also exhibited significantly higher levels of negative and disorganised symptoms, making it unclear whether lower GAF scores were due to more marked functional impairment or more severe negative and disorganised symptoms in this group.…”
Section: Anxietymentioning
confidence: 93%
“…This assumption is based also on studies of subjects at CHR that report similar but more attenuated findings compared to those reported for schizophrenia, including cognitive impairments, [26][27][28] structural, [29][30][31][32] and functional alterations. 33,34 Moreover, characterizing those at the prepsychotic phase of illness, who evince potential prodromal symptoms, is critical for establishing biomarkers that can be used to follow the effects of treatment or to identify subjects who are at higher risk for developing the illness.…”
Section: Introductionmentioning
confidence: 95%
“…Overall, sample-size weighted mean prevalence rates show that 12.1% (CI: 9.4–14.8%) of ARMS patients report OCS (Shioiri et al, 2007; Niendam et al, 2009; Bechdolf et al, 2011; Sterk et al, 2011; Hur et al, 2012), while 5.2% (CI: 4.1–6.3%) fulfill the criteria for OCD (Shioiri et al, 2007; Niendam et al, 2009; Rubino et al, 2009; Bechdolf et al, 2011; Fontenelle et al, 2011; DeVylder et al, 2012; Fusar-Poli et al, 2012; Sterk et al, 2011) (Figure 1A). Slightly higher averaged rates for OCS (17.1%, CI: 14.0–20.2) and OCD (7.3%, CI: 5.3–9.3%) can be found in first episode patients (Figure 1B; Poyurovsky et al, 1999a; de Haan et al, 2004; Sterk et al, 2011; de Haan et al, 2012; Zink et al, under review).…”
Section: Clinical Presentation and Explanatory Conceptsmentioning
confidence: 99%
“…Regarding the impact of OCS during the ARMS on other clinical variables, findings have been heterogeneous. Whereas higher impairment of psychosocial functioning (de Haan et al, 2012; DeVylder et al, 2012; Fusar-Poli et al, 2012; Hur et al, 2012) and more severe depressive symptoms (Niendam et al, 2009; DeVylder et al, 2012; Fontenelle et al, 2012; de Haan et al, 2013) have consistently been reported, findings regarding transition rates into psychosis (Niendam et al, 2009; Fontenelle et al, 2011, 2012; Fusar-Poli et al, 2012) and cognition (Van Dael et al, 2011){4854}(Hur et al, 2012) are contradicting.…”
Section: Clinical Presentation and Explanatory Conceptsmentioning
confidence: 99%